Modulation of glucocorticoid receptor function under iron overload - Zhu, Wanting; Vanderhaeghen, Tineke; Timmermans, Steven; Vandewalle, Jolien; Eggermont, Melanie; Verhoog, Nicolette J. D.; Libert, Claude (Frontiers in Immunology, 2025)
Acute iron overload leads to ferroptosis, in a mouse model of FeSO4 challenge causing lethal shock, associated with inflammation and multiple organ failure (MOF). We investigated molecular aspects causing this phenomenon upon FeSO4 overload, with a focus on the glucocorticoid receptor (GR), an important anti-inflammatory transcription factor. We report that Fe overload activates the HPA axis, leading to corticosterone increases in the blood, acutely causing upregulation of GR-dependent genes in liver. Using a GR blocker, mice with a reduced GR dimerization potential and removal of adrenal glands sensitizes mice for Fe-induced toxicity, GR appears essential to resist ferroptosis. However, stimulating GR with DEX is unable to protect mice against FeSO4-induced MOF and death. This dilemma is shown, by RNA sequencing, to be the result of a quick and complete inactivation of GR biological function by Fe2+, shortly after the initial activation. This inactivity of GR seems to be the result of a complete lack of GR to bind its ligand. We discuss the possible mechanism and complications for ferroptosis progression during diseases.